1994
DOI: 10.1099/0022-1317-75-11-3177
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Functional Regions of the Cucumber Mosaic Virus RNA Replicase Using Monoclonal and Polyclonal Antibodies

Abstract: Monoclonal antibodies were produced using a purified cucumber mosaic virus (CMV) replicase complex, and Escherichia coli-expressed CMV la and 2a proteins, as immunogens. Five out of eight monoclonal antibodies, which bound to the la and 2a proteins in immunoblots, inhibited the RNA-dependent RNA polymerase (RdRp) activity of the purified replicase complex in vitro. Epitope mapping showed that two of the inhibitory antibodies interacted with regions of the la protein containing putative helicase and methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…The inhibition of the template-dependent RCNMV RNA polymerase by antibodies to a peptide containing the GDD motif shows that the region of the polymerase containing this motif is accessible to the antibodies. A similar finding was made with an RNA-dependent RNA polymerase of cucumber mosaic virus (CMV), the activity of which was inhibited by antibodies to a peptide containing the GDD motif of the CMV 2a protein (Hayes et al, 1994). On the basis of conservation of this or equivalent motifs in DNA-and RNA-dependent RNA and DNA polymerases, Delarue et al (1990) suggested that the basic structure of all these polymerases may be similar.…”
Section: Discussionmentioning
confidence: 77%
“…The inhibition of the template-dependent RCNMV RNA polymerase by antibodies to a peptide containing the GDD motif shows that the region of the polymerase containing this motif is accessible to the antibodies. A similar finding was made with an RNA-dependent RNA polymerase of cucumber mosaic virus (CMV), the activity of which was inhibited by antibodies to a peptide containing the GDD motif of the CMV 2a protein (Hayes et al, 1994). On the basis of conservation of this or equivalent motifs in DNA-and RNA-dependent RNA and DNA polymerases, Delarue et al (1990) suggested that the basic structure of all these polymerases may be similar.…”
Section: Discussionmentioning
confidence: 77%
“…In some experiments, the RNA polymerase was incubated with purified MBP-fusion protein or MBP (10 g) at 0°C for 30 min prior to the addition of the antibodies. Control experiments to check that the antibodies were free from ribonuclease activity were carried out as described previously (2,20).…”
Section: Solubilization and Purification Of The Tmv-l Rna Polymerasementioning
confidence: 99%
“…The sodium taurodeoxycholatesolubilized polymerase was used for further purification. No attempt was made to remove the endogenous bound RNA template at this stage, since viral RNA polymerases bound to their templates have been found to be more stable through subsequent purification stages (2,20).…”
Section: Solubilization Of the Tmv-l Membrane-bound Rna Polymerase Anmentioning
confidence: 99%
“…For example, antibody-mediated inhibition of proteolytic processing of poliovirus polypeptide P3-7c (Hanecak et al, 1982), and inhibition of RNA-dependent RNA polymerase in a purified replicase complex of cucumber mosaic virus (Hayes et al, 1994). Our previous results have shown that recombinant nsP2 and its N-terminal fragment possess NTPase activity.…”
Section: Discussionmentioning
confidence: 99%